أساليب تدريب المعلمين أثناء الخدمة في ظل الامكانات المادية الشحيحة من وجهة نظر موجهي المرحلة الثانوية بولاية النيل الأبيض - د . محمد الامين محمد يوسف كبر (White Nile Journal for Studies and Research, 2018)
The research intends to recognize some training programs which are available to be carried out without much cost, besides, the factors negatively affect teacher training, and the obstacles which face secondary school teachers training. The researcher used descriptive method and questionnaire as aresearch tool. The research population consisted of all secondary stage supervisors and from them thirty had been randomly chosen as a research sample. The most important results are: Discussions groups, model lessons, and electronictraining may be considered as programs do not cost much. Also, weak teachers education before practicing profession, weak budget, and traditional methods used in training are considered factors negatively affect training programs. The obstacles face teacher training are lack of modern training aids, high cost of equipment's, and absence of coordination among departments related to training. The most important recommendations are, related teachers upgrading with compulsory training programs, making use of retired teachers in training, and encourage directed self-reading.